Adverse outcome and severity of COVID‐19 in patients with autoimmune bullous diseases: A historical cohort study. Issue 9 (21st July 2022) - Moghadam, Fateme Shirzad; Kianfar, Nika; Dasdar, Shayan; Samii, Rana; Farimani, Zeinab; Azar, Pedram Molhem; Balighi, Kamran; Abedini, Robabeh; Soori, Tahereh; Farid, Ali Salehi; Mahmoudi, Hamidreza; Daneshpazhooh, Maryam
Abstract: The ongoing COVID‐19 pandemic has raised concerns regarding the outcome of this infection in patients with autoimmune bullous dermatoses (AIBDs) due to effect of drugs used to treat these disorders. This investigation was performed from the onset of the pandemic to June 1, 2021. Patients with AIBDs who contracted COVID‐19 were evaluated. A generalized linear model was employed to find the predictors of severe COVID‐19 among patients with AIBDs. Ninety‐three patients with AIBDs with a mean age of 50.3 years were evaluated. The most COVID‐19 related symptoms were tiredness (76.3%) myalgia (69%), and cough (63.4%). During follow‐up, the rate of hospitalization and death were 45.2% and 4.3%, respectively. Previous comorbidities (β = 0.61) and mean prednisolone dosage above 10 mg/day in the last 3 months ( β = 1.10) significantly increased COVID‐19 severity. Also, vaccination against SARS‐CoV‐2 ( β = −1.50) and each passing month from the last rituximab dose decreased severity ( β = −0.02). Notably, 19.3% of the patients developed AIBD flare‐ups following COVID‐19 infection. Higher prednisone dose and the shorter interval from the last rituximab infusion were determinants of severe COVID‐19. Physicians should assess the risk versus the benefits when prescribing the medications. Moreover, vaccination could successfully attenuate COVID‐19 severity.